2009
DOI: 10.3174/ajnr.a1806
|View full text |Cite
|
Sign up to set email alerts
|

Voxel-Based Analysis of Diffusion Tensor Imaging in Mild Traumatic Brain Injury in Adolescents

Abstract: BACKGROUND AND PURPOSE: DTI of normal-appearing WM as evaluated by conventional MR imaging in mTBI has the potential to identify important regional abnormalities that relate to PCS. VBA was used to examine WM changes in acute mTBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
103
3
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(123 citation statements)
references
References 36 publications
9
103
3
8
Order By: Relevance
“…A priori ROIs were selected based on previous publications in semi-acute pmTBI Chu et al, 2010;Maugans et al, 2012) and our adult samples (Ling et al, 2012b). ROIs included the genu, splenium and body of the CC, the corona radiata [anterior (ACR) and superior (SCR)], cingulum, combined anterior and posterior limbs of the IC, and the cerebral peduncles (CP) for both the right and left hemispheres.…”
Section: Methodsmentioning
confidence: 99%
“…A priori ROIs were selected based on previous publications in semi-acute pmTBI Chu et al, 2010;Maugans et al, 2012) and our adult samples (Ling et al, 2012b). ROIs included the genu, splenium and body of the CC, the corona radiata [anterior (ACR) and superior (SCR)], cingulum, combined anterior and posterior limbs of the IC, and the cerebral peduncles (CP) for both the right and left hemispheres.…”
Section: Methodsmentioning
confidence: 99%
“…The clinical implications of FA change remain controversial, as both increased and decreased FA has been observed in concussion studies. [162][163][164][165][166] These discrepancies may be due, in part, to the considerable spatial heterogeneity in the brain areas examined, 167 as well as differences in the postinjury interval. FA may still have prognostic value, with evidence suggesting that the direction and magnitude of change correlates with clinical outcomes; 166,168 however, this idea awaits validation in both paediatric and adult populations.…”
Section: Fluid-based Biomarkersmentioning
confidence: 99%
“…Using advanced quantitative techniques such as diffusion-tensor imaging, Little et al ( 40 ) showed reductions in fractional anisotropy in several white matter regions when fi ber tracking seeds were placed in the thalamic nuclei in a mixed group of patients with mild and moderate to severe injury. Other studies involving diffusion-tensor imaging and proton MR spectroscopy ( 41,42 ) revealed only minimal detectable differences in the thalamus between the MTBI and control groups. Ge et al ( 43 ) recently reported decreased cerebral fl ow in the thalamus in MTBI, suggesting blood fl ow compromise in these patients.…”
Section: Neuroradiology: Thalamic Resting-state Functional Network DImentioning
confidence: 99%